Poor recognition of other-race faces cannot always be explained by a lack of effort. Issue 4 (3rd July 2017) - Crookes, Kate; Rhodes, Gillian
ABSTRACT: People are generally better at recognizing own-race than other-race faces. This "other-race effect" is very well established although the underlying causes are much debated. Social-cognitive accounts argue that the other-race effect stems from a lack of motivation to individuate other-race faces, whereas perceptual expertise accounts argue that it reflects the tuning of face-processing mechanisms by experience to own-race faces. We investigated the effort people apply to recognize own-race and other-race faces. Caucasian participants completed the Australian and Chinese Cambridge Face Memory Tasks, once with the standard timing and once with self-paced study phases. If people are less motivated to recognize other-race faces they should apply less effort, that is, when given control over viewing times they should spend less time studying other-race than own-race faces. Contrary to social-cognitive accounts, there was no evidence of reduced effort for other-race faces. Participants did not spend less time studying other-race than own-race faces in the self-paced condition. Moreover, participants reported applying significantly more effort to telling apart other-race than own-race faces. These results are not consistent with reduced motivation to individuate other-race faces. Thus, they appear more consistent with perceptual expertise rather than social-cognitive accounts of the other-race effect.